Accurate Reliability Evaluation and Enhancement via Probabilistic Transfer Matrices - Krishnaswamy, Smita; Viamontes, George F.; Markov, Igor L.; Hayes, John P. (Design, Automation and Test in Europe, 2005)
Soft errors are an increasingly serious problem for logic circuits. To estimate the effects of soft errors on such circuits, we develop a general computational framework based on probabilistic transfer matrices (PTMs). In particular, we apply them to evaluate circuit reliability in the presence of soft errors, which involves combining the PTMs of gates to form an overall circuit PTM. Information such as output probabilities, the overall probability of error, and signal observability can then be extracted from the circuit PTM. We employ algebraic decision diagrams (ADDs) to improve the efficiency of PTM operations. A particularly challenging technical problem, solved in our work, is to simultaneously extend tensor products and matrix multiplication in terms of ADDs to non-square matrices. Our PTM-based method enables accurate evaluation of reliability for moderately large circuits and can be extended by circuit partitioning. To demonstrate the power of the PTM approach, we apply it to several problems in fault-tolerant design and reliability improvement.